EFL Students' Perception on Vocabulary Learning with Quizlet - Djamdjuri, Dewi Suriyani; Thoyib, Mastur; Retnowati, Nanik; Furqan, Muhammad; Holifah, Muharani (STKIP PGRI SITUBONDO, 2023)
Vocabulary plays a crucial role in communication and is considered one of the important aspects of the English language. Insufficient vocabulary knowledge can impede the process of learning English. Technology can serve as a valuable option for learning English vocabulary, as it provides various resources such as language learning apps that can enhance vocabulary and language skills. Quizlet is one such application that assists students in learning vocabulary concepts interactively and enjoyably. Student perceptions in learning activities are important things to know. This study aims to find out how students perceive the use of the Quizlet application in learning vocabulary whether they have negative or positive perceptions. This study uses qualitative methods in data collection. Ten students from grade seven became participants in this study. Researchers used two instruments, namely questionnaires and interviews. After distributing the questionnaires to students, the researcher also conducted interviews with five students to obtain more detailed information. The results showed that students had a positive perception of using Quizlet.